Notes on Advertisement Calls Playback by Three Species of Sarawakian Frogs - Ramlah, Zainudin; Muhammad Fadzil, Amran; Hasnizam, Abdul Wahid (UNIMAS Publisher, 2020)
Male and female frogs respond differently towards advertisement calls. The fittest call will be chosen by the conspecific female to produce progenies, means that call from male to female is to ensure the survival of the species. The objective is to observe the response of both male and female frogs by playing the advertisement call to another male or female of the same species at their breeding site. The advertisement calls were recorded manually and were replayed using a speaker with built-in amplifier. The frog’s responses were then recorded in video form. Ambient temperatures were taken using data logger. The calls were analyzed to describe call characteristics. From the acoustic playback, both male and female Pulchrana glandulosa responded towards the calls. The male produces a crying-like sound while approaching playback source meanwhile the female produces a small “wik” sound. Male Pulchrana baramica responded by straining their calls and approaches the playback source. For male Kurixalus appendiculatus, the individuals responded by moving towards the sound source without calling. Results show that male of different species and male and female of the same species react differently towards playback calls. This shows that the breeding call recorded can be recognized by other frogs when they were played on amplifier.